(3GdHSjW aj GdJaSjQs - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj GdfjSGHhQj, J (B468 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ bhdg JYGdi (B:" (3hGPcQhG Gddg ai CjGe eYOhOGJ (B" (3ef ShQI GdHbQ s
(3BNQgG (B:s
(3jfJgi HJaSjQ bhdg JYGdi (B:" (3MQeJ Ydjce CegGJce hHfGJce (B" (3GdBjI ef ShQI GdfSGA s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3JaSjQ (B51) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs